Dangers of Decentralisation in Urban Slums: A Comparative Study of Water Supply and Drainage Service Delivery in Kolkata, India. (2nd February 2016) - De, Indranil; Nag, Tirthankar
Abstract : Clientelism may lead to the underprovision of services which are deemed suitable for decentralisation. Water distribution and drainage services, managed from a lower level of municipal authority, are liable to be affected by clientelism and consequent underprovision. Water quality, maintained from a higher municipal layer, is not likely to be affected by clientelism. Capture by politically influential and dominant social and religious groups is likely to take place for important services like water supply. The article suggests that awareness, measurability, importance and resource intensiveness of service are additional factors to be considered for assessing the suitability of a sector for decentralisation.